Zwitterionic 1-{(1E)-[(4-hydroxyphenyl)iminio]methyl}naphthalen-2-olate: crystal structure and Hirshfeld surface analysis - Devika, Bhai R.; Girija, C. R.; Shalini, Suresh; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2017)
The title zwitterion, C17H13NO2 (systematic name: 1-{(1E)-[(4-hydroxyphenyl)iminiumyl]methyl}naphthalen-2-olate), features an intramolecular charge-assisted N+—H...O− hydrogen bond. A twist in the molecule is evident around the N—C(hydroxybenzene) bond [C—N—C—C torsion angle = 39.42 (8)°] and is reflected in the dihedral angle of 39.42 (8)° formed between the aromatic regions of the molecule. In the crystal, zigzag supramolecular chains along the a axis are formed by charge-assisted hydroxy-O—H...O(phenoxide) hydrogen bonding. These are connected into a layer in the ab plane by charge-assisted hydroxybenzene-C—H...O(phenoxide) interactions and π–π contacts [inter-centroid distance between naphthyl-C6 rings = 3.4905 (12) Å]. Layers stack along the c axis with no specific interactions between them. The Hirshfeld surface analysis points to the significance C...H contacts between layers.